STABLE OXYGEN ISOTOPE SOURCING OF ARCHAEOLOGICAL FAUNA FROM CHACO CANYON, NEW MEXICO. Issue 1 (16th November 2017) - Hamilton, Marian I.; Drake, B. Lee; Wills, W. H.; Jones, Emily Lena; Conrad, Cyler; Crown, Patricia L.
Abstract : Modern datasets provide the context necessary for accurate interpretations of isotopic data from archaeological faunal assemblages. In this study, we use the oxygen isotope ratios (δ 18 O) of modern small mammals from Chaco Canyon, New Mexico, to quantify expected isotopic variation in a local population. The δ 18 O values of local, modern small mammals encompass a broad range (−6.0‰ to 4.8‰ VPDB), which is expected given the extreme seasonal variation in the δ 18 O of precipitation on the Colorado Plateau (−11‰ to −3‰ VPDB). Isotopic ratios of small mammals obtained from excavated archaeological sites in Chaco Canyon (ca. AD 800 to 1200) show no significant differences with their modern counterparts, suggesting that there is no difference in the origins of the archaeological small-mammal collection and the modern, local Chaco Canyon small-mammal collection. In contrast, δ 18 O values of large mammals from Chaco archaeological sites are significantly different from those of modern specimens, reflecting a nonlocal, but also nonspecific, source in the past. Abstract : Los datos isotópicos de los animales modernos pueden proporcionar información importante para la interpretación de los datos isotópicos procedentes de conjuntos faunísticos arqueológicos. En este estudio utilizamos las proporciones de isótopos de oxígeno (δ 18 O) de pequeños mamíferos modernos en Chaco Canyon, Nuevo México, para cuantificar la variación esperada para una única población local. El rango de valores de δ 18 O de los pequeños mamíferos locales en Chaco Canyon es amplio (-6, 0‰ a 4, 8‰ VPDB). Esto no es sorprendente, dada la considerable variación estacional de δ 18 O ligada a la precipitación en la meseta del Río Colorado (-11‰ a -3‰ VPDB). Las proporciones isotópicas de los pequeños mamíferos arqueológicos procedentes de los sitios excavados en Chaco Canyon (ca. 800–1200 dC) no difieren de manera significativa de las de los animales modernos. Esto sugiere que no hay diferencias de procedencia entre la colección arqueológica de pequeños mamíferos y los mamíferos locales modernos de Chaco Canyon. En cambio, los valores de δ 18 O de los mamíferos grandes de los sitios arqueológicos de la zona son muy distintos de los valores de mamíferos grandes modernos. Esto sugiere que los especímenes de mamíferos grandes arqueológicos tienen origen diferente y no local, aunque no especulamos sobre dónde pudo haber sido ese lugar.